2008
DOI: 10.1016/j.nut.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of hydrolyzable tannins-rich pomegranate extract suppresses inflammation and joint damage in rheumatoid arthritis

Abstract: Objective-Although consumption of dietary supplements containing pomegranate extract by arthritis patients is on the rise, efficacy of such preparations in suppressing joint inflammation and damage is not known. The present study was designed to evaluate a standardized preparation of pomegranate extract (POMx) using collagen-induced arthritis in mice (CIA)-a widely used animal model of rheumatoid arthritis (RA).Methods-CIA susceptible DBA/1 mice were fed POMx by gavage before and after immunization with chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 41 publications
6
131
0
2
Order By: Relevance
“…Antioxidant and antibacterial properties of pomegranate peel in in-vitro model systems have been reported (Negi and Jayaprakasha, 2003;Reddy et al, 2007;Opara et al, 2009;Alzoreky 2009). As the study says that Benzene extract of Pomegranate fruit peel can inhibit the population of both Pseudomonas aeruginosa and Salmonella typhi respectively which is already shown by many scientist like Lansky, 2005;Al-Zoreky, 2009;Gould et al, 2009;Machado et al, 2003;Opara et al, 2008 in their study which was on antimicrobial activity of pomegranate has been documented with different extracts and the potential therapeutic applications of the antimicrobial properties of pomegranate components have been investigated in human and murine models (Jurenka, 2008;Basu, 2009;Aviram et al, 2008;Betanzos et al, 2011;Sumner et al, 2005;Rock et al, 2008;Rosenblat et al, 2006;Shukla et al, 2008). However, FPJ antimicrobial activity has not been explored in spite of its high content of antioxidants.…”
Section: Antibacterial Screeningmentioning
confidence: 82%
“…Antioxidant and antibacterial properties of pomegranate peel in in-vitro model systems have been reported (Negi and Jayaprakasha, 2003;Reddy et al, 2007;Opara et al, 2009;Alzoreky 2009). As the study says that Benzene extract of Pomegranate fruit peel can inhibit the population of both Pseudomonas aeruginosa and Salmonella typhi respectively which is already shown by many scientist like Lansky, 2005;Al-Zoreky, 2009;Gould et al, 2009;Machado et al, 2003;Opara et al, 2008 in their study which was on antimicrobial activity of pomegranate has been documented with different extracts and the potential therapeutic applications of the antimicrobial properties of pomegranate components have been investigated in human and murine models (Jurenka, 2008;Basu, 2009;Aviram et al, 2008;Betanzos et al, 2011;Sumner et al, 2005;Rock et al, 2008;Rosenblat et al, 2006;Shukla et al, 2008). However, FPJ antimicrobial activity has not been explored in spite of its high content of antioxidants.…”
Section: Antibacterial Screeningmentioning
confidence: 82%
“…Administration of tannic acid to mice, for example, has been demonstrated to suppress inflammation and joint damage in rheumatoid arthritis (19). Another study in mice demonstrated that tannic acid not only possesses its own scavenging activity of free radicals but the compound also directly acts upon and reduces negative effects of the cytochrome P450 pathway implicated in DNA mutagenesis and cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…6 Consumption of pomegranate extract potently delayed the onset and reduced the incidence of collagen-induced arthritis and severity of arthritis was significantly lower in pomegranate extract fed animals. 7 In this review, we summarize the therapeutic role of pomegranate in the diseases managements based on in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%